2016
DOI: 10.1186/s40862-016-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

An emic perspective toward challenges and solutions of self- and peer-assessment in writing courses

Abstract: Self-assessment and peer-assessment have been appraised in a large number of studies, aiming at investigating their effectiveness in different contexts. However, the challenges of implementing self-assessment and peer-assessment have been investigated rather sporadically. Given that, the purpose of this study was to explore the challenges and probable solutions of implementing self-assessment and peer-assessment by delving into the perspectives of English language teaching (ELT) teachers and ELT students. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The results revealed that collaboration among team members leads to many opportunities for idea exchanging and peer feedback. Meihami and Razmjoo (2016) investigated the challenges and solutions of utilizing self-and peer-assessment in writing courses. By conducting a series of interviews and open-ended questions, Meihami and Razmjoo delved into the perspectives of 11 English Language Teaching (ELT) teachers and 56 ELT students to find out their challenges and probable solutions to applying self-and peer-assessment in the writing classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that collaboration among team members leads to many opportunities for idea exchanging and peer feedback. Meihami and Razmjoo (2016) investigated the challenges and solutions of utilizing self-and peer-assessment in writing courses. By conducting a series of interviews and open-ended questions, Meihami and Razmjoo delved into the perspectives of 11 English Language Teaching (ELT) teachers and 56 ELT students to find out their challenges and probable solutions to applying self-and peer-assessment in the writing classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nakamura (2002) reported that (a) the teacher assessor was more lenient than the peer-assessors were, but the peer-assessors varied in their levels of severity and leniency; (b) peer-assessment was successful in motivating students to improve their oral skills; and (c) students as peer-assessors could be reasonably reliable raters of their peers. Meihami and Razmjoo (2016) investigated the challenges and solutions of utilizing self-and peer-assessment in writing courses. By conducting a series of interviews and open-ended questions, Meihami and Razmjoo (2016) delved into the perspectives of 11 ELT teachers and 56 ELT students to find out their challenges and probable solutions to applying self-and peer-assessment in the writing classes.…”
Section: Studies On Self-assessment Peer-assessment and Teacher Assmentioning
confidence: 99%
“…Meihami and Razmjoo (2016) investigated the challenges and solutions of utilizing self-and peer-assessment in writing courses. By conducting a series of interviews and open-ended questions, Meihami and Razmjoo (2016) delved into the perspectives of 11 ELT teachers and 56 ELT students to find out their challenges and probable solutions to applying self-and peer-assessment in the writing classes. The results of their study indicated that ELT students thought of self and peer's subjective judgment, learners' lack of assessment literacy, and instructional problems as the main challenges of self-and peer-assessment in writing classes.…”
Section: Studies On Self-assessment Peer-assessment and Teacher Assmentioning
confidence: 99%
“…This is due to the reason that students might give higher marks to their teammates [9,10]. There are several factors that can influence the self-discipline of students such as nature of a subject, number of products or performance assessed, gender difference, racial and cultural background [12,13]. From the findings of a previous study, the gender-based differences may influence the transparency of a student whilst doing the assessment [14].…”
Section: Ethicsmentioning
confidence: 99%